1981
DOI: 10.1901/jaba.1981.14-345
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcer Variation: Implications for Motivating Developmentally Disabled Children

Abstract: Motivating developmentally disabled children to participate in educational activities can be very difficult. This is especially true for children diagnosed autistic. Because there is some evidence to suggest that stimulus variation may influence motivation, the present study investigated the effects of constant vs. varied reinforcer presentation on correct responding and on-task behavior. Results from a reversal design showed declining trends in both correct responding and on-task behavior when the same reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
4
8

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 19 publications
7
90
4
8
Order By: Relevance
“…First, as we have noted, providing such choices may accommodate shifts in preferences that occur over time. Second, in most cases, providing presession or within-session choices increases reinforcer variation, which can reduce or prevent satiation (e.g., Bowman, Piazza, Fisher, Hagopian, & Kogan, 1996;Egel, 1981). Third, providing choices may be reinforcing, which can add to the reinforcement value of the selected item (Catania & Sagvolden, 1980;.…”
Section: Resultsmentioning
confidence: 99%
“…First, as we have noted, providing such choices may accommodate shifts in preferences that occur over time. Second, in most cases, providing presession or within-session choices increases reinforcer variation, which can reduce or prevent satiation (e.g., Bowman, Piazza, Fisher, Hagopian, & Kogan, 1996;Egel, 1981). Third, providing choices may be reinforcing, which can add to the reinforcement value of the selected item (Catania & Sagvolden, 1980;.…”
Section: Resultsmentioning
confidence: 99%
“…Egel (1980) found that the scheduling of multiple edible reinforcers produced more bar press responses and faster responding than single edible reinforcers in 10 autistic children. Of greater relevance to our study, Egel (1981) found that multiple edibles produced more responses and higher percentages of correct responding and on-task behavior than single edibles in classroom discination tasks with three autistic children. Egel's (1981) subjects (range: 8-64) than in ours (range: 80-190).…”
Section: Discussionmentioning
confidence: 50%
“…Of greater relevance to our study, Egel (1981) found that multiple edibles produced more responses and higher percentages of correct responding and on-task behavior than single edibles in classroom discination tasks with three autistic children. Egel's (1981) subjects (range: 8-64) than in ours (range: 80-190). This difference may in turn be due to Egel's use of a more restrictive satiation criterion than ours (viz., three no-response trials vs. 50% no-response trials in two blocks of 10 trials), to the use of three teacher-nominated edibles as reinforcers instead of five empirically validated edibles, or to subject, task, or other procedural differences.…”
Section: Discussionmentioning
confidence: 50%
“…Egel (1980) observed that the pre-sentation of varied reinforcers produced higher response rates than did the presentation of any one of the reinforcers singly. He subsequently extended those findings to classroom performance (Egel, 1981).…”
Section: ____________________________________________________________mentioning
confidence: 94%
“…One of these factors is repeated exposure to the same reinforcer, which may result in performance decrements that often are attributed to satiation or habituation. Egel (1980Egel ( , 1981 conducted a series of studies showing that this problem may be alleviated by varying the stimuli that are delivered as reinforcers. Egel (1980) observed that the pre-sentation of varied reinforcers produced higher response rates than did the presentation of any one of the reinforcers singly.…”
Section: ____________________________________________________________mentioning
confidence: 99%